Review of the Guidelines For Radiology Practice During COVID -19 Pandemic by Nepal Radiologists’ Association - Jha, Anamika; Suwal, Sundar; Karki, Dan Bahadur; Ghimire, Ram Kumar (Nepalese Journal of Radiology, 2020)
Nepal is also affected by Corona Virus Disease (COVID-19) pandemic which is likely to last for several months. The Reverse Transcriptase-Polymerase Chain Reaction is the current gold standard diagnostic test. Chest X-ray or Computed Tomography scan is considered inappropriate according to most society recommendations for screening though are emerging as frontline diagnostic modalities in conjunction with clinical history and laboratory parameters. Multiple guidelines have been released by prominent radiological societies worldwide to facilitate preparedness of radiology department in the war against COVID-19. Based on these, the Nepal Radiologists’ Association has proposed its guidelines, endorsed by the Nepal Medical Council, practical in our context, with the aim to limit exposure to the infection while ensuring best use of imaging, protection of health care personnel and other patients and maintenance of uninterrupted radiology department operations. This review article aims to summarize the highlights from various guidelines focusing on role of chest X-ray and Computed Tomography including the indications, specific findings, reporting format and important differentials and also addresses the safety issues.